Educar para as relações étnico-raciais : mudanças no campo normativo e o impacto no mercado editorial - Madeira, Thais Fernanda Leite (2016)
Education has always been considered by social movements, especially the black movement, as an important playing field to be included in their discussions, as it is understood to be a means of promoting awareness, appreciation and social inclusion. Therefore, the approval of Law no. 10.639 / 2003 and its guidelines, which amended the Education Law (Lei de Diretrizes e Bases, or LDB, in Portuguese), can be considered a new milestone in the history of education in Brazil, because they represent substantial changes that alter the country's educational policy and reflect profound social changes in the way our society is represented. Compulsory education about ethno-racial relations and the history of Afro-Brazilian and African culture in all primary and secondary education reverberates in textbooks and supplementary course material, seen as important tools that play a key role to promote the history, culture and identity of Brazilians of African descent and erradication of prejudices. It is understood that publishers occupy an important space, creating, editing and disseminating textbooks and educational material; in other words, structured spaces that permit the transfer of symbolic capital for the legitimation of discourse and the discussion of topics of interest related to social demands, dictating themes and directing debates. In this context, the objective of this study is to investigate the publishing market in the Brazilian context, identifying how changes in the legal field have impacted its dynamics, starting from theNational Textbook Program and the National School Library Program.